Aortic dysfunction in metabolic syndrome mediated by perivascular adipose tissue TNFα‐ and NOX2‐dependent pathway. Issue 4 (28th February 2018) - DeVallance, Evan; Branyan, Kayla W.; Lemaster, Kent; Olfert, I. Mark; Smith, David M.; Pistilli, Emidio E.; Frisbee, Jefferson C.; Chantler, Paul D.
Abstract : New Findings: What is the central question of this study? Tumour necrosis factor‐α (TNFα) has been shown to impair vascular function, but the impact of thoracic aorta perivascular adipose tissue (tPVAT)‐derived TNFα on tPVAT and aortic function in metabolic syndrome is unknown. What is the main finding and its importance? Release of TNFα by tPVAT causes production of reactive oxygen species in tPVAT through activation of an NADPH‐oxidase 2 (NOX2)‐dependent pathway, activates production of aortic reactive oxygen species and mediates aortic stiffness, potentially through matrix metalloproteinase 9 activity. Neutralization of TNFα and/or inhibition of NOX2 blocks the tPVAT‐induced impairment of aortic function. These data partly implicate tPVAT NOX2 and TNFα in mediating the vascular pathology of metabolic syndrome. Abstract: Perivascular adipose tissue (PVAT) is recognized for its vasoactive effects, but it is unclear how metabolic syndrome impacts thoracic aorta (t)PVAT and the subsequent effect on functional and structural aortic stiffness. Thoracic aorta and tPVAT were removed from 16‐ to 17‐week‐old lean (LZR, n  = 16) and obese Zucker rats (OZR, n  = 16). The OZR presented with aortic endothelial dysfunction, assessed by wire myography, and increased aortic stiffness, assessed by elastic modulus. The OZR tPVAT exudate further exacerbated the endothelial dysfunction, reducing nitric oxide and endothelium‐dependent relaxation ( P  < 0.05). Additionally, OZR tPVAT exudate had increased MMP9 activity ( P  < 0.05) and further increased the elastic modulus of the aorta after 72 h of co‐culture ( P  < 0.05). We found that the observed aortic dysfunction caused by OZR tPVAT was mediated through increased production and release of tumour necrosis factor‐α (TNFα; P  < 0.01), which was dependent on tPVAT NADPH‐oxidase 2 (NOX2) activity. The OZR tPVAT release of reactive oxygen species and subsequent aortic dysfunction were inhibited by TNFα neutralization and/or inhibition of NOX2. Additionally, we found that OZR tPVAT had reduced activity of the active sites of the 20S proteasome ( P  < 0.05) and reduced superoxide dismutase activity ( P  < 0.01). In conclusion, metabolic syndrome causes tPVAT dysfunction through an interplay between TNFα and NOX2 that leads to tPVAT‐mediated aortic stiffness by activation of aortic reactive oxygen species and increased MMP9 activity. Abstract :